A Review on Talibids' Genealogy - Mohammadreza Alemi, Seyyed (تاریخ اسلام)
In the first Islamic century, genealogy of Talibids was not so broad and this field like the other Arabs' kinship was registered in the general kinship books of Arabs and Quraish but since the end of the third century considering the religious instructions and the position of prophet's household before Muslims and particularly Shiites, it was developed specialized genealogy of Talibids. At first, to write the kinship of Talibids, it was being utilized the general sources of genealogy but regularly and  affected by chiefs' relationships (Naqibs) and genealogists under their observation, the writing about the kinship of Talibids considerably increased and its sources gradually got up to date and efficient. Most authors of Talibids' kinship are of Shiites and Talibids  but among them are mostly Imamid writers. Utilizing kinship books, this writing is to deliver a valid narration and analysis of the trend of the development of Talebids' genealogy and its relationship with the rank of leadership, the area and the mode of relationship as well as the features of genealogists and their sources.